2018
DOI: 10.1111/pace.13415
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and electrophysiological properties of atrial tachycardia after pediatric heart transplantation

Abstract: In this cohort, the most common form of AT after pediatric heart transplantation was focal, with predilection for sites near the crista terminalis. Transplant patients with AT experienced a higher rate of clinical rejection and the composite end-point of retransplantation or death relative to unaffected controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Ivabradine was not observed to be effective for arrhythmia control in the patient with posttransplant atrial tachycardia. Failure of ivabradine in this case likely relates to an underlying mechanism of microreentry rather than enhanced automaticity; in a recent series, 78% of focal atrial tachycardias in pediatric heart transplant recipients were nonautomatic 6 . Together, the presented cases provide further evidence that ivabradine is a safe and potentially effective therapy for arrhythmias with a mechanism of enhanced automaticity, and add to the emerging literature on the role of ivabradine as an antiarrhythmic agent.…”
Section: Discussionmentioning
confidence: 58%
“…Ivabradine was not observed to be effective for arrhythmia control in the patient with posttransplant atrial tachycardia. Failure of ivabradine in this case likely relates to an underlying mechanism of microreentry rather than enhanced automaticity; in a recent series, 78% of focal atrial tachycardias in pediatric heart transplant recipients were nonautomatic 6 . Together, the presented cases provide further evidence that ivabradine is a safe and potentially effective therapy for arrhythmias with a mechanism of enhanced automaticity, and add to the emerging literature on the role of ivabradine as an antiarrhythmic agent.…”
Section: Discussionmentioning
confidence: 58%
“…Various reports show that these alternative mechanisms are frequent in pediatric and adult patients with and without congenital heart disease. (17)(18)(19) In addition, increased automaticity -and thus pacemaker activity -are not solely dependent on HCN channels, which are the electrical target for ivabradine treatment. Enhanced function of other ionic channels and their currents may also be responsible for spontaneous diastolic depolarizations in selected patients with automatic FAT, rendering them insensitive to ivabradine.…”
Section: Clinical Experience With Ivabradinementioning
confidence: 99%
“…However, during the last decade, performed investigations in the USA transplant centers revealed that supraventricular tachycardia could affect approximately 10% or more of cardiac transplant recipients. Moreover, they demonstrated that during heart transplant surgery, complicated modifications of the atrial substrate could be followed by both proarrhythmic and antiarrhythmic consequences which are mainly dependent on the performed surgical procedure [31,32]. Indeed, during heart transplantation, surgical modification of the atria causes antiarrhythmic consequences such as vagal denervation and pulmonary vein isolation, as well as proarrhythmic consequences, for instance, the creation of atriotomy scar [33].…”
Section: Arrhythmiamentioning
confidence: 99%